Analysis of trip cutting behavior of jeepneys and UV express with respect to LRT Line 2 Santolan and Katipunan stations - Andres, Carlos Miguel; Fernandez, John Roy E.
Trip-cutting of public utility vehicles in the Philippines, especially jeepneys, and recently UV Express, has been a habit of the drivers, cutting short of their franchised route. Although trip-cutting is considered to be a traffic violation according to various local and national laws, this has been widely practiced by the drivers, especially in road corridors which experience heavy traffic volume. In this study, the conditions along the Santolan and Katipunan stations of the LRT Line 2 will be inspected. Trip cutting tendencies were characterized and evaluated by conducting 12-hour traffic volume surveys for a period of five (5) days in four (4) different study areas, as well as conducting interviews with the concerned PUV drivers. At the end of this study, it has been proven that trip-cutting behavior of PUV drivers traversing along the study area is a common practice, and the certain overlying factors involve trip-cutting behavior by PUV drivers were identified.